ADVERTISING AND PROMOTION FOR INCLUSIVE GROWTH OF PRODUCT AND SERVICES - Reddy, Dr. J. V. Rangeswara (IJRDO - Journal of Business Management, 2016)
Advertising is bringing a product or service to the attention of potential and current customers. Advertising is focused on one particular product or service. Thus, an advertising plan for one product might be very different than that for another product. In another way we can say “advertisement is any paid form of non-personal presentation of ideas, goods, and services through an identified sponsor”. Promotion keeps the product in the minds of the customer and helps simulate demand for the product. Promotion involves ongoing advertising and publicity. Advertising is a creating a market for the product. Without advertising the product may not be launched or sold in the market. Creating awareness through advertisement becomes a common practice for the organization it is common practice that the advertisement expenditure is a hidden expenditure for the product promotion. Advertisement is a creating a value for the product in the competitive market. Improper promotion of the product may lead to the failure for the product in the market. Quality, quantity and design will not create a value but advertisement gives value with creative interest on the product for buying it. AIDA (attention, interest, desire and action) is most important for any type of product advertisement. Interest and awareness creation is possible only with the advertisement. Media selection play vital role in the promotion activities of the product and services in the market.